Increasing Knowledge of Nurses in Managing Disaster Victims using Rehearsal Simulation: Tabletop Disaster Exercise - Putra Agina Widyaswara Suwaryo; Hendri Tamara Yuda; Eko Budi Santoso; Aprilia Safaroni (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Management of disaster victims carried out by nurses needs to be based on good knowledge in order to save many lives. It is necessary to carry out optimal strategies and exercises in providing management of disaster victims. The Space Rehearsal Simulation using the tabletop disaster exercise method was able to increase the knowledge and analytical power of the medical team, especially nurses, in providing management for disaster victims. This activity was carried out using online and offline methods for 3 meetings consisting of preparation, implementation, and evaluation. Participants are nurses who are active in disaster activities totaling 16 people. The media used are disaster maps, simulation scenarios and cases, and observation sheets. The results showed that knowledge increased, the average before was 47.81 and the average after was 88.43. The rehearsal simulation method using tabletop disaster is an alternative method that is simple and practical to increase nurses' knowledge.